Iowa CBC reporting form, Jamaica, December 24, 1985 - Cummins, Raymond L.et al (1985)
Checklist dated December 24, 1985 compiled by Ray Cummins. A list of birds sighted by Cummins and six others around Jamaica. A total of 52 species and 4846 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed